Organic filling mitigates flaw-sensitivity of nanoscale aragonite - Cruz-Chú, Eduardo Roberto; Patil, Sandeep Parasharam; Gräter, Frauke (ACS biomaterials science & engineering, 2017)
Engineering at nanoscale holds the promise of tuning materials with extraordinary properties. However, macroscopic approaches commonly used to predict mechanical properties do not fully apply at nanoscale level. A controversial feature is the presence of nanoflaws in aragonite nacre, as it is expected that flaws would weaken the material, whereas nacre still shows high toughness and rupture strength. Here, we performed molecular dynamics and finite element simulations emulating flaws found in aragonite nacre. Our simulations reveal two regimes for fracture: nacre remains flaw-insensitive only for flaws smaller than 1.2 nm depth, or flaws of a few atoms, whereas larger flaws follow a Griffith-like trend resembling macroscopic fracture. We tested an alternative mechanism for flaw-insensitivity in nacre, and investigated the mechanical effect of organic filling to mitigate fracture. We found that a single nacre protein, perlucin, decreases the stress concentration at the fracture point, producing enhancements of up to 15% in rupture strength. Our study reveals a more comprehensive understanding of mechanical stability at the nanoscale and offers new routes toward hybrid nanomaterials.